2016
DOI: 10.1097/mej.0000000000000280
|View full text |Cite
|
Sign up to set email alerts
|

A case management intervention targeted to reduce healthcare consumption for frequent Emergency Department visitors: results from an adaptive randomized trial

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
86
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(89 citation statements)
references
References 16 publications
3
86
0
Order By: Relevance
“…All of the studies included development and implementation of a care plan, 15 involved an interdisciplinary team, [40][41][42][43][45][46][47][49][50][51]53,[55][56][57][58] and 11 were conducted in an ED setting. 41,43,44,47,[49][50][51][52]55,57,58 For the majority of studies (n = 17), CM intervention participants were identified using a threshold of number of health care visits. [40][41][42][43][44][46][47][48][49][50][52][53][54][55][56][57]59 To determine eligibility, 9 studies required patients be evaluated by a health care provider to assess their likelihood of benefiting from the CM intervention.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…All of the studies included development and implementation of a care plan, 15 involved an interdisciplinary team, [40][41][42][43][45][46][47][49][50][51]53,[55][56][57][58] and 11 were conducted in an ED setting. 41,43,44,47,[49][50][51][52]55,57,58 For the majority of studies (n = 17), CM intervention participants were identified using a threshold of number of health care visits. [40][41][42][43][44][46][47][48][49][50][52][53][54][55][56][57]59 To determine eligibility, 9 studies required patients be evaluated by a health care provider to assess their likelihood of benefiting from the CM intervention.…”
Section: Resultsmentioning
confidence: 99%
“…41,43,44,47,[49][50][51][52]55,57,58 For the majority of studies (n = 17), CM intervention participants were identified using a threshold of number of health care visits. [40][41][42][43][44][46][47][48][49][50][52][53][54][55][56][57]59 To determine eligibility, 9 studies required patients be evaluated by a health care provider to assess their likelihood of benefiting from the CM intervention. 42,44,[47][48][49]51,52,55,58 Ten studies included patients with a complex/vulnerable situation such as the presence of physical, psychiatric, and/or psychosocial issues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[3] Frequent users (FUs usually ≥ 4 visits during 12 months) have been suggested as an important reason for ED crowding. [4] In this article, we identified the characteristics of double frequent users (DFUs), ≥ 8 visits during 12 months and at least 25 visits to ED during a period of six years. The primary outcome was to understanding reasons for frequent visits to the ED.…”
Section: Introductionmentioning
confidence: 99%